PENGARUH STRUKTUR ASET, PERTUMBUHAN PENJUALAN, PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, DAN CASH HOLDING TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Novrian Puji Hartanto, 14.05.52.0300; Nurhayati, Ida (Students Journal of Accounting and Banking, 2017)
This research was conducted with the aim to analyze the effect of the structure of assets, sales growth, profitability, liquidity, cash holding company size and the capital structure. This research was done because of the problem of capital structure is important for the company, where the merits of the companys capital structure will have a direct effect on its financial position. Independent variables used in this study is the structure of assets, sales growth, profitability, liquidity, and cash holding company size, while the dependent variable used is Yag capital structure. Researchers used the lull one btahun between dependent and independent variables, where it is assumed that the policy that occurred in year t is the result of consideration of the factors influencing the previous year t (t-1). The data used in this study are data companies listed in Indonesia Stock Exchange (BEI) during the years 2013-2015. Methods in the selection of the sample in this study using purposive sampling method with the purpose to obtain a sample in accordance with the purpose of research. This study of 194 of the sample data on manufacturing companies in the Indonesia Stock Exchange. The hypothesis in this study were tested using multiple linear regression analysis with a confidence level of 95%. The results showed that: (1) there is significant relationship between asset structure terhada capital structure, (2) there is no significant effect anatara sales growth with asset structure, (3) there is significant between profitability on capital structure, (4) there was no significant effect of liquidity on the capital structure, (5) there is significant relationship between the size of companies on capital structure, and (6) a significant difference between holding cash on the capital structure.Keywords:Â Asset Structure, Growth Sales, Profitability, Liquidity, Company Size, and Cash Holding